A LOOK AT THE ZAKIROV DYNASTY - Togaymurodov J. K. (Web of Journals Publishing, 2024)
In this article, based on the theme "A look at the work of the People's Artist of Uzbekistan, Botir Zakirov, who made a great contribution to the Uzbek national pop art", the works and decisions are being made to perpetuate the memory of Botir Zakirov.
Keywords: Music, art, national pop, artist, singer, painter, artist, composer, composer, work, tune, song, conductor, instrument performance.